1991
DOI: 10.1200/jco.1991.9.4.592
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in long-term survivors of CNS tumors of childhood and adolescence.

Abstract: Clinical reports of small numbers of pediatric brain tumor patients observed for brief periods suggest that long-term survivors continue to have major handicaps into adulthood. To quantify these late effects we interviewed 342 adults (or their proxies) who had CNS tumors diagnosed before the age of 20 between 1945 and 1974, survived at least 5 years, and reached 21 years of age. Survivors were 32 years old on average at follow-up. When compared with 479 matched siblings as controls. CNS tumor survivors were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1
4

Year Published

1993
1993
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(89 citation statements)
references
References 26 publications
2
82
1
4
Order By: Relevance
“…6 Previous studies have considered marriage and parenthood as important indicators of psychological adjustment and achievement of social life goals by cancer survivors. 8,9 Most retrospective cohort and case-control studies conducted in the US, Canada and UK found marriage rates to be lower than expected, especially among survivors of childhood central nervous system (CNS) cancer, [9][10][11][12][13][14] and reported treatment-related fertility deficits. [15][16][17][18][19] In Italy, the only attempts to assess the experience of marriage and parenthood of childhood cancer survivors have been carried out in a single region situated in the North-West of the country (representing approximately 7% of the whole Italian population) using data of the Childhood Cancer Registry of Piedmont.…”
Section: Introductionmentioning
confidence: 99%
“…6 Previous studies have considered marriage and parenthood as important indicators of psychological adjustment and achievement of social life goals by cancer survivors. 8,9 Most retrospective cohort and case-control studies conducted in the US, Canada and UK found marriage rates to be lower than expected, especially among survivors of childhood central nervous system (CNS) cancer, [9][10][11][12][13][14] and reported treatment-related fertility deficits. [15][16][17][18][19] In Italy, the only attempts to assess the experience of marriage and parenthood of childhood cancer survivors have been carried out in a single region situated in the North-West of the country (representing approximately 7% of the whole Italian population) using data of the Childhood Cancer Registry of Piedmont.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive literature has arisen on the medical costs of cure and the late effects of treatment (Blatt & Bleyer, 1989;Chessells et al, 1981;Green et al, 1991;Lansky et al, 1987; Levine & Hersh, 1982;Links & Stockwell, 1985;Maguire et al, 1987;Meadows et al, 1981Meadows et al, , 1980Mostow et al, 1991;Nesbit et al, 1979;O'Malley et al, 1979;Pastore et al, 1987;Wheeler et al, 1988;Whitt et al, 1984). This literature has identified a wide variety of seqpielae of ALL.…”
mentioning
confidence: 99%
“…In particular, brain radiotherapy continues to pose a challenge to radiation oncologists because of the negative effects in neurocognitive, neuroendocrine function, and hearing loss. Neurocognitive damage is demonstrated by a development of deficits in several areas including mathematic ability, language, attention, memory, sleep-wake rhythm and Intelligence Quotient (IQ) [8]. Negative neurocognitive effects are the result of several factors including the brain tumor itself disrupting neurocognitive functioning, hydrocephalus, operative approaches and peri-operative complications.…”
Section: Tumors Of the Central Nervous Systemmentioning
confidence: 99%